Early Experience with the Use of Inner Branches in Endovascular Repair of Complex Abdominal and Thoraco-abdominal Aortic Aneurysms. (May 2018) - Katsargyris, Athanasios; Marques de Marino, Pablo; Mufty, Hozan; Pedro, Luis Mendes; Fernandes, Ruy; Verhoeven, Eric L.G.
Abstract : Objectives: Visceral arteries in fenestrated and branched endovascular repair (F/BEVAR) have been addressed by fenestrations or directional side branches. Inner branches, as used in the arch branched device, could provide an extra option for visceral arteries "unsuitable" for fenestrations or directional side branches. Early experience with the use of inner branches for visceral arteries in F/BEVAR is described. Methods: All consecutive patients treated by F/BEVAR for complex abdominal aortic aneurysm (AAA) or thoraco-abdominal aneurysm (TAAA) using stent grafts with inner branches were included. Data were collected prospectively. Results: Thirty-two patients (28 male, mean age 71.6 ± 8.3 years) were included. Seven (21.9%) patients had a complex AAA and 25 (78.1%) had a TAAA. A stent graft with inner branches only was used in four (12.5%) patients. The remaining 28 (87.5%) patients received a stent graft with fenestrations and inner branches. In total 52 vessels were targeted with inner branches. Technical success was achieved in all 32 (100%) patients. All 38 inner branch target vessels in grafts including fenestrations and inner branches were instantly catheterised (<1 minute), whereas catheterisation of target vessels in "inner branch only" grafts proved more difficult (<1 minute, n = 3; 1–3 min, n = 4; and >3 min, n = 7). The 30 day operative mortality was 3.1% (1/32). Estimated survival at 1 year was 80.0% ± 8.3%. During follow-up, four renal inner branches occluded in three patients. The estimated inner branch target vessel stent patency at 1 year was 91.9 ± 4.5%. The estimated freedom from re-intervention at 1 year was 78.4% ± 8.9%. Conclusions: Early data suggest that visceral inner branches might represent a feasible third option to address selected target vessels in F/BEVAR. Stent grafts with inner branch(es) in combination with fenestrations seem to be a better configuration than stent grafts with inner branches alone. Durability of the inner branch design needs further investigation.